Scale of Consumer Motivation on Business Performance in SMEs in Yogyakarta - Nina Fapari Arif; Fathi Habibatur Rahman; Siti Khusnul Rifani; Ansri Jayanti; Tasrim (Yayasan Putra Adi Dharma, 2023)
Business Permanence is a series of integrated business activities so that a business can grow or survive in the face of challenges and competition. BP is generally determined by financial and non-financial aspects. This research examines business performance from a non-financial aspect, namely from the consumer aspect. This research uses the Consumer Motivation Scale Theory approach. From this theory, it is classified into three scales, namely Economic, Hedonic, and Normative Purpose. These three scales become independent variables for business performance. The research object is UKM located around tourist attractions in Yogyakarta. Observation results show that these UKMs operate in the culinary, souvenir, accommodation and ornamental plants sectors. The population is consumers who visit these SMEs. The research sample was 50 respondents with sampling using the accidental random sampling method. The data analysis used is multiple linear regression. The results show 1) Economic Purpose influences Business Performance with a significance value of 0.002 < 0.05 and a calculated t value of 3.247 > t table 2.160, 2) Hedonic Purpose influences Business Performance with a significance value of 0.013 < 0.05 and a calculated t value 2.597 > t table 2.160, 3) Normative Purpose influences Business Performance with a significance value of 0.028 < 0.05 and a calculated t value of 2.269 > t table 2.160.